HUBUNGAN POLA ASUH ORANG TUA DENGAN KEDISIPLINAN SISWA KELAS V GUGUS I HANG NADIM KECAMATAN TAMPAN KOTA PEKANBARU - Lestari, Rizki Lestari Rizki; ', Syahrilfuddin Syahrilfuddin; ', Hamizi Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Problems in this research started from the observation that many researchers see morality offense committed by such elementary students arriving late to school, do not wear full attribute during the ceremony, throwing garbage out of place, and others. The cause is suspected as the provision of parenting is not appropriate. This research is done to determine the relationship of parenting parents with discipline students in class V Cluster I Hang Nadim District of Tampan Pekanbaru conducted in three schools namely SDN 136 Pekanbaru, Pekanbaru SDN 137, SD IT Darul Hikmah. This research is a quantitative research by using correlational approach. The population in this research was 376 students and samples as many as 93 students by using systematic sampling technique. Researchers get the data using questionnaire instrument. Data were obtained and then tested the validity and reliability using SPSS version 17. To test whether the data were normally distributed or not, is done with Lilliefors test. Then the data were analyzed using Pearson Product Moment formula to determine the relationship of parenting parents (X) with student discipline (Y). Results of the analysis of this study showed no significant relationship between parenting parents authoritarian, democratic, permissive, and neglectful with discipline graders V Cluster I Hang Nadim District of Tampan Pekanbaru. Where the authoritarian parenting has t_ (count)> t_tabel or 5.6172> 1.671, democratic parenting has t_ (count)> t_tabel or 4.5738> 1.671, permissive parenting has t_ (count)> t_tabel or3.9028> 1,671, neglectful parenting has t_ (count)> t_tabel or 3.1071> 1.671.Keyword: Parenting Parents, Discipline Students